Héctor Alimonda, the American task of political ecology (Alternautas, 2022)
This text is an introduction of Alternautas’ mini-dossier in tribute to the work of Hector Alimonda (1947-2017). Here, Facundo Martín, Gabriela Merlinsky and Catalina Toro Pérez present Alimonda’s unique contribution to the field of political ecology in Latin America. It is followed by the newly translated “In the key of south: Latin American political ecology and critical thinking”, the introduction of Alimonda’s latest book, Ecología Política Latinoamericana - Volumen 1 (2017), co-edited by Facundo Martín and Catalina Toro Pérez. In the next weeks, we will also publish a translation of “The coloniality of nature”, an article that appeared originally in La naturaleza colonizada (2011).